Indefinite readings of referential null subjects and null objects in Spanish - Martínez García, Carlos (Borealis – An International Journal of Hispanic Linguistics, 2023)
It has been claimed in the literature that referential null subjects receive definite readings in consistent null-subject languages, like Spanish. That is why they are said to display the typical behavior of definite pronouns (pro). However, referential null subjects can receive indefinite readings under the following conditions: i) the antecedent must be a bare plural, ii) the indefinite null argument is interpreted as a bare noun, typically as an internal argument, and iii) identity of sense anaphora is involved. Crucially, referential null objects appear under the same conditions, and receive indefinite readings in Peninsular Spanish. This suggests that the gap could be analyzed in the same way. In this paper, I argue that both null arguments should not be analyzed as empty pronominals (pro), given the syntactic behavior that they show. By contrast, I will argue that an argument ellipsis analysis should be assumed, given that the internal argument position is occupied by an indefinite, non-specific bare noun, the null gap can receive sloppy readings, and the omission is not as ‘big’ as the one at verb-stranding VP-ellipsis, nor as ‘small’ as the one at nominal ellipsis.